Determinants of Firm Value: A Study on Telecommunication Companies in Indonesia - Alysia Oktaviany; Dwianto Mukhtar Latif (P3M Politeknik Negeri Banjarmasin, 2021)
This study was conducted to determine the effect of Return on Assets, Debt to Equity Ratio, Current Ratio, Total Assets Turnover and Company Size on Price to Book Value as a proxy for Firm Value in Telecommunication Companies Listed on the Indonesia Stock Exchange for the 2012-2017. The research method used is quantitative. The population in this study was all telecommunications sector companies listed on the Indonesia Stock Exchange in 2012-2017 (5 companies, 30 data). Samples were taken using the census technique. The data analysis technique used multiple linear regressions. The results of the research that have been carried out show that: (1) Return on Assets, Current Ratio and Company Size have no effect on Price to Book Value of Telecommunication Companies Listed on the Indonesia Stock Exchange for the 2012-2017 period; (2) Debt to Equity Ratio and Total Asset Turnover have a positive effect on Price to Book Value of Telecommunication Companies Listed on the Indonesia Stock Exchange for the 2012-2017